Search for supersymmetry in events with b-quark jets and missing transverse energy in pp collisions at 7 TeV - Chatrchyan, S. (2012)
Results are presented from a search for physics beyond the standard model based on events with large missing transverse energy, at least three jets, and at least one, two, or three b-quark jets. The study is performed using a sample of proton-proton collision data collected at √s=7TeV with the CMS detector at the LHC in 2011. The integrated luminosity of the sample is 4.98fb -1. The observed number of events is found to be consistent with the standard model expectation, which is evaluated using control samples in the data. The results are used to constrain cross sections for the production of supersymmetric particles decaying to b-quark-enriched final states in the context of simplified model spectra. © 2012 CERN. Published by the American Physical Society.